PENGARUH SOSIALISASI PERPAJAKAN DAN PERSEPSI WAJIB PAJAK TENTANG PELAKSANAAN SENSUS PAJAK NASIONAL TERHADAP KESADARAN WAJIB PAJAK ORANG PRIBADI (Survei Terhadap Wajib Pajak Orang Pribadi Di Wilayah Banyuwangi) - Kurniawan, Herlambang (Jurnal Mahasiswa Perpajakan, 2014)
The purpose of this research is to find the effect of between the Socialization of Taxation and Taxpayer Perception on the Implementation of National Tax Census simultaneously and partially on Individual Taxpayer Awareness. The type of research is eksplanatory with the quantitative approach. The data collection method use form of questionnaire. Samples of 100 Individual Taxpayer has been recorded in the census by tax officer. The data analysis is descriptive and multiple linear regression. The results of research showed Socialization of taxation and taxpayer perception on the implementation of the National Tax Census simultaneously effect significantly on Taxpayer Awareness. Socialization of Taxation partially effect significantly on Taxpayer Awareness. Taxpayer Perception on the Implementation of the National Tax Census partially effect significantly on Taxpayer Awareness. The results test of determination coefficient showed that Socialization of Taxation, and Taxpayer Perception on the Implementation of the National Tax Census simultaneously give effect of 59,3% on Taxpayer Awareness. Variable that more dominant effect of Individual Taxpayer Awareness is Socialization of Taxation. Key words: socialization of taxation, taxpayer perception, national tax census, taxpayer awareness.